Arsenic trioxide blocked proliferation and cardiomyocyte differentiation of human induced pluripotent stem cells: Implication in cardiac developmental toxicity. (July 2019) - Bao, Zhengyi; Han, Zhenbo; Zhang, Bo; Yu, Ying; Xu, Zihang; Ma, Wenya; Ding, Fengzhi; Zhang, Lai; Yu, Meixi; Liu, Shenzhen; Jin, Mengyu; Yan, Gege; et al.
Highlights: Indicating the toxicity of ATO in cardiomyocytes differentiation. Finding that ATO blocked cardiomyocyte differentiation, induced apoptosis and cell growth arrest. Providing safety guidence for the clinical application of ATO. Abstract: Arsenic trioxide (ATO) has been recommended as the first-line agent for the treatment of acute promyelocytic leukaemia (APL), due to its substantial anticancer effect. Numerous clinical reports have indicated that ATO is a developmental toxicant which can result in birth defects of human beings. But whether arsenic trioxide can lead to human cardiac developmental toxicity remains largely unknown. So the present study aims to explore the influence and mechanisms of ATO on human cardiac development by using a vitro cardiac differentiation model of human induced pluripotent stem cells (hiPSCs). Here we found that clinically achievable concentrations (0.1, 0.5 and 1 μM) of ATO resulted in a significant inhibition of proliferation during the whole process of cardiac differentiation of hiPSCs. Meanwhile, TUNEL assay revealed that ATO could cause cell apoptosis during cardiac differentiation in a concentration-dependent manner. Consistently, we found that ATO reduced the expressions of mesoderm markers Brachyury and EOMES, cardiac progenitor cell markers GATA-4, MESP-1 and TBX-5, and cardiac specific marker α-actinin in differentiated hiPSCs. Furthermore, ATO treatment had caused DNA damage which was shown in the upregulation of γH2AX, a sensitive marker for DNA double-strand breaks. Taken together, ATO blocked cardiomyocyte differentiation, induced apoptosis and cell growth arrest during cardiac differentiation of hiPSCs, which might be associated with DNA damage.